Optimalisasi Pemasaran Produk Lokal Melalui Workshop Desain Grafis Dengan Canva pada Koperasi Wanita - Sanwani, Sanwani; Priyatna, Ade; Budi, Eko Setia; Zuraidah, Eva; Perwitasari, Ayu; Anggata, Aprio Riska; Agustina, Menik Anna; Krishandi, Septa Remond; Nursalim, Fredrika Irmanielyn (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Atsiri Women's Cooperative is a social organization as a forum and means of developing every member of society that grows and develops on the basis of social awareness and responsibility from and for the community in the region, especially engaged in medium and small businesses. While the membership of the Atssiti Citayem Cooperative, hereinafter referred to as the Cooperative Mothers, is every member of the community. Atsiri Women's Cooperative, Established on December 11, 2011, located at Jl. Jalan Sedap Malam Raya no 45 Rt 01 RW 12 Atsiri Permai Housing, Ragajaya Village, Bojonggede District. Bogor Regency. Postal Code 16920, Deed of Establishment of the